Problems with evaluating readings of pulse oximeters used at home during the ongoing COVID-19 pandemic - Cysewska-Sobusiak, Anna Romana (Photonics Letters of Poland, 2021)
The author presents the problems related to pulse oximetry, taking into account both the current state-of-the-art as well as her own long-standing experience in this field. The COVID-19 pandemic continues and has raised interest in home application of pulse oximeters due to their potential benefit, which may be warning of a drop in blood oxygenation due to lower respiratory capacity. However, it should be emphasized that these devices have limitations, both of a physiological and technical nature, and some problems related to the reliability and scope of the measurements still remain unresolved. Phenomena which limit processing reliability of the quantity to be sensed, i.e., the oxygen saturation SaO2%, are presented. Specific groups of affecting factors are distinguished in an approach of their contribution to the measurement uncertainty components. Full Text: PDF References J.W. Severinghaus, "Crediting six discoverers of oxygen", Adv. Exp. Med. Biol. 812 (2014). CrossRef F.A. Duck, "Physical properties of tissue: a comprehensive reference book" (San Diego, Academia Press 1990). CrossRef J.G. Webster, "Design of pulse oximeters" (Bristol, IOP Publishing Ltd 1997). CrossRef A.A. Alian and K.H Shelley, "Photoplethysmography", Anesthesiology 28, 4 (2014). CrossRef N. Moukaddam and A. Shah, "Psychiatrists beware! The impact of COVID-19 and pandemics on mental health", Psychiatric Times 37, 3 (2020). CrossRef S.S. Morse, Proc Nat. Acad Sci 104, 18 (2007). CrossRef W.A. Schrading, B. McCafferty, J. Grove, and D.B. Page, "Portable, consumer‐grade pulse oximeters are accurate for home and medical use: Implications for use in the COVID‐19 pandemic and other resource‐limited environments", JACP Open, 1 (2020). CrossRef K.E.J. Philip, B. Bennet, S. Fuller, et al., "Working accuracy of pulse oximetry in COVID-19 patients stepping down from intensive care: a clinical evaluation ", BMJ Open Resp. Res. 7 (2020). CrossRef S. Seifi, A. Khatony, G. Moradi, A. Abdi, and F. Najafi, "Accuracy of pulse oximetry in detection of oxygen saturation in patients admitted to the intensive care unit of heart surgery: comparison of finger, toe, forehead and earlobe probes", BMC Nursing 17, 15 (2018). CrossRef A. Cysewska-Sobusiak, "A modern approach to the determination of expanded uncertainty in noninvasive blood oximetry", Measurement 25 (1999). CrossRef A. Cysewska-Sobusiak, "The importance of the combined teaching and research work in the education of biomedical engineering", Biocybernetics and Biomedical Engineering 22, 4 (2002). CrossRef A. Cysewska-Sobusiak, "Noninvasive optoelectronic monitoring of the living tissues vitality", 3rd Int. Workshop on Robot Motion and Control, Nov. 2002 (2002). CrossRef A. Cysewska-Sobusiak, "Examples of acquisition and application of biooptical signals", Phot. Lett. Poland 11, 2 (2019). CrossRef